Kualitas Pelayanan Publik Di Kecamatan Kaliorang Kabupaten Kutai Timur Provinsi Kalimantan Timur (Suatu Studi Pelayanan Administrasi Kependudukan Di Kecamatan Kaliorang) - Nanik Pujiastuti (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2016)
Quality of service is a State-related capability meets the desires of customers so the gap between the expectations with the reality of the case. Quality should be started from the need of customers and end on customer perception. Dotted with decline in the explanation above, the authors are interested in conducting research with the title "quality of public services in district of East Kutai Regency Kaliorang, East Kalimantan province (a Study Population in district administrative service Kaliorang)" In line with the needs of the community will be a quality service from the Government, then as a public servant who gained the trust of the community, the Government should always refer to the satisfaction of the community which is the purpose of a staple in the granting of Ministry. One form of government services is a service of the administration of the settlement, particularly the service ID CARD. Based on the results of the study it can be concluded that in general the quality of public services in district hasn't fulfilled Kaliorang properly. It can be seen from the five dimensions of service quality, namely: Tangibles, Reability, Responsivess, Assurance and Empathy.